ASSESSING THE INDONESIAN CONSTITUTIONAL COURT CONSISTENCY IN DETERMINING ITS AUTHORITY TO SETTLE DISPUTE ON REGIONAL HEAD ELECTION - Andy Omara (Yustisia Jurnal Hukum, 2020)
This study aims to answer three important questions: first, how the 1945 Constitution regulate the authority of the Constitutional Court in resolving dispute on general election as stated in Article 22 E and the regional head election as stipulated in Article 18. Second, how the Constitutional Court, through its rulings, interpret its authority to settle dispute on general election and regional head election. Third, why, in different period, there is a tendency that the Court provide different interpretation regarding its authority to resolve dispute on general election and regional head election. To answer these three questions, this study utilizes doctrinal approach. It analyses the relevant laws and regulation and also the relevant Court rulings. This study concludes that (1) the 1945 Constitution expressly differentiate between regional head election and general election. However, (2) the Court provide different interpretation on determining the nature of regional head election specifically on whether such an election include in the category of general election or it is a distinct election. (3) There are two main factors that may explain why the Court provide different explanation regarding its power to settle dispute on the regional head election and general election.